Anthropogenic sulphur dioxide load over China as observed from different satellite sensors. (November 2016) - Koukouli, M.E.; Balis, D.S.; van der A, Ronald Johannes; Theys, N.; Hedelt, P.; Richter, A.; Krotkov, N.; Li, C.; Taylor, M.
Abstract: China, with its rapid economic growth and immense exporting power, has been the focus of many studies during this previous decade quantifying its increasing emissions contribution to the Earth's atmosphere. With a population slowly shifting towards enlarged power and purchasing needs, the ceaseless inauguration of new power plants, smelters, refineries and industrial parks leads infallibly to increases in sulphur dioxide, SO2, emissions. The recent capability of next generation algorithms as well as new space-borne instruments to detect anthropogenic SO2 loads has enabled a fast advancement in this field. In the following work, algorithms providing total SO2 columns over China based on SCIAMACHY/Envisat, OMI/Aura and GOME2/MetopA observations are presented. The need for post-processing and gridding of the SO2 fields is further revealed in this work, following the path of previous publications. Further, it is demonstrated that the usage of appropriate statistical tools permits studying parts of the datasets typically excluded, such as the winter months loads. Focusing on actual point sources, such as megacities and known power plant locations, instead of entire provinces, monthly mean time series have been examined in detail. The sharp decline in SO2 emissions in more than 90%–95% of the locations studied confirms the recent implementation of government desulphurisation legislation; however, locations with increases, even for the previous five years, are also identified. These belong to provinces with emerging economies which are in haste to install power plants and are possibly viewed leniently by the authorities, in favour of growth. The SO2 load seasonality has also been examined in detail with a novel mathematical tool, with 70% of the point sources having a statistically significant annual cycle with highs in winter and lows in summer, following the heating requirements of the Chinese population. Highlights: SCIAMACHY/Envisat, OMI/Aura and GOME2/MetopA SO2 columns over China are presented. Monthly mean time series of megacities and known power plant locations are examined. 90% of the locations studied show a sharp decline in SO2 emissions this past decade. 70% of the locations have a statistically significant annual cycle with highs in winter. The implementation of government desulphurisation legislation over China is effective.